Evaluation of different personalized ventilation air terminal devices: Inhalation vs. clothing-mediated exposures. (April 2021) - Al Assaad, Douaa; Ghali, Kamel; Ghaddar, Nesreen; Katramiz, Elvire; Ghani, Saud
Abstract: Human exposure to particles indoors occurs through direct inhalation or indirectly through deposition on clothes that release them in other spaces. Ventilation systems are installed to decrease direct exposure but little is known about their effect on clothing-mediated exposures. This work weighs the effect of personalized ventilation (PV) systems on decreasing inhalation exposure to indoor particles versus their contribution to clothing contamination by particle deposition. To conduct this work, a 3D computational fluid dynamics model was developed for an office conditioned by mixing ventilation and common PV air terminal devices: computer mounted panel (CMP), vertical desk grill (VDG) and round movable panel (RMP). Typical particle sources were considered: furniture resuspension and human breathing. The model was validated experimentally in a climatic chamber by comparing real-time particle mass concentration near a thermal manikin. Results showed that CMP delivering 5 l/s reduced total inhalation exposure by 27% and deposition by 72% compared to standalone mixing ventilation. Increasing the flow to 10 l/s led to reductions of 89% in exposure and 56.5% in deposition. A VDG delivering 5 l/s reduced exposure by 33% while deposition reduction was negligible at 3%. Increasing the flow rate to 10 l/s reduced exposure by 91% and slightly increased deposition by 12%. The RMP at 5 l/s and 10 l/s reduced exposure by 89% and 97% respectively and increased deposition by 70% and 80% respectively. Among the three ATDs, the CMP offered the best compromise between reducing inhalation exposure and clothing-mediated exposures at all possible flow rates. Graphical abstract: Image 1 Highlights: Performance of 3 PV ATDs: Inhalation exposure (iF) & clothing contamination (DFr). 3D CFD model of an office with MV + PV was developed and validated experimentally. CMP reduced iF by max of 89% & DFr by max 72% at 5 l/s compared to standalone MV. VDG reduced iF by max 91% but increased DFr by max 12% at 10 l/s compared to MV. RMP reduced iF by max 97% but increased DFr by max 80% at 10 l/s compared to MV.